A Case Study of Drug Prevention in the United States of America (The Role of Marketing) - Caroon, Lindsey; Saeed, M (Journal of Commerce and Trade, 2009)
Societal Marketing plays a positive role in preventing the use of illegal drugs and addictive substances. There is a dire need to strengthen the role of ethical advertisers and public service announcements, for creating a pattern of responsible consumer behavior, while regulatory measures are required to discipline the industrialists and marketers against their negative role. This study examines historical backdrop and looks in particular at the Surgeon General’s Report on Preventing Tobacco Use Among Young People as a case in point. Marketers are experts in understanding behavior. If prevention educators are able to better understand behavior, and have a better understanding of the marketing principles used the influence it, then they will be better equipped to effect change.